PENGARUH PENAMBAHAN GLUKOSA DAN SARI BUAH JERUK (Citrus sinensis) TERHADAP KARAKTERISTIK MINUMAN SINBIOTIK CINCAU HIJAU (Premna oblongifolia Merr.) - Anjelia Putri; Tirza Hanum; Samsul Rizal; Sri Setyani (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
This study was aimed to determine the concentration of orange juice (Citrus sinensis) and glucose which produce green cincau sinbiotic beverage with the best characteristics, has high concentration of lactic acid bacteria and antioxidant activity as well as good sensory properties. Factorial treatment was arranged in a Complete Randomized Block Design with two factors and three replications. The first factor was the concentration of orange juice (J), consisted of 5 levels (0%, 5%, 10%, 15%, and 20%), and the second factor was the concentration of glucose (K) that consisted of 3 levels (2%, 3%, and 4%). The homogeneity and additivity of the data were analyzed using Barlett and Tuckey tests. Then the ata were analyzed with Analysis of Varians, and further analyzed using orthogonal polynomials on the significant level of 5% or 1%. The results showed that the addition of 2% glucose and 0% orange juice produced the best characteristics of green cincau sinbiotic beverage with concentration of lactic acid bacteria 4,59 x 1010 colonies/ml, total acid 0,29%, pH 4,13, antioxidant activity of 54,88% RSA, taste of 3,52 (like), colors of 2,87 (rather like), and flavor of 2,95 (rather like). Keyword : antioxidant, green cincau, sinbiotic